Impact of 18F-fluciclovine PET/CT on salvage radiotherapy plans for men with recurrence of prostate cancer postradical prostatectomy. Issue 2 (19th October 2021) - Payne, Heather; Bomanji, Jamshed; Bottomley, David; Scarsbrook, Andrew F.; Teoh, Eugene J.; ,
Abstract : Objectives: Imaging options to localize biochemical recurrence (BCR) of prostate cancer after radical prostatectomy (RP) are limited, especially at low prostate-specific antigen (PSA) levels. The FALCON study evaluated the impact of 18 F-fluciclovine PET/CT on management plans for patients with BCR. Here, we evaluate salvage radiotherapy decisions in patients post-RP. Methods: We conducted a subgroup analysis of post-RP patients enrolled in FALCON who had a prescan plan for salvage radiotherapy (± androgen-deprivation therapy). Patients' treatment plans post- 18 F-fluciclovine PET/CT were compared with their prescan plans. Fisher exact test was used to determine the impact of PSA and Gleason sum on positivity and anatomical patterns of uptake. Results: Sixty-five (63%) FALCON patients had undergone RP. Of these, 62 (median PSA, 0.32 ng/mL) had a prescan plan for salvage radiotherapy. Twenty-one (34%) had 18 F-fluciclovine-avid lesions. Disease was confined to the prostate bed in 11 patients (52%) and to the pelvis in a further 5 (24%), while 5 (24%) had extrapelvic findings. Trends towards more disseminated disease with increasing PSA or Gleason sum were observed but did not reach statistical significance. Postscan, 25 (40%) patients had a management change; 17 (68%) were changed to the treatment modality (8 to systemic therapy, 8 to active surveillance, 1 other) and 8 (32%) were radiotherapy field modifications. Conclusions: Incorporating 18 F-fluciclovine PET/CT into treatment planning may help identify patients suitable for salvage radiotherapy, help augment planned radiotherapy to better target lesions and support the clinician to optimise patient management.